SPECTROSCOPIC STUDIES AND ANTIBACTERIAL ACTIVITY GREEN SYNTHESIZED NEWLY IMINOTHIAZOLIDINONE DERIVATIVES - Tugcu, Fatma Tulay (CHEM SOC ETHIOPIA, 2025)
Ten novel iminothiazolidinone derivatives were synthesized via a green, solvent-free, one-pot multicomponent reaction involving aryl-substituted thioureas, chloroacetic acid, and various thiophene-2-carboxaldehydes. The reaction proceeded under mild conditions without the use of catalysts, fulfilling the key criteria of sustainable synthetic methodology. Structural elucidation of the synthesized compounds was achieved through FT-IR, 1H-NMR, 13C-NMR, mass spectrometry, and elemental analysis, confirming the formation of the iminothiazolidinone core. The antibacterial activity of the compounds was evaluated using the agar diffusion method against Gram-positive bacteria including Staphylococcus aureus, Bacillus subtilis, and Staphylococcus epidermidis. Compound 4 exhibited the highest antibacterial effect across all tested strains. Cytotoxicity studies using the HEK-293 cell line demonstrated that Compound 4 also showed the most favorable safety profile, with no significant toxicity observed at concentrations near its antibacterial efficacy. These results suggest that the synthesized iminothiazolidinones are promising scaffolds for the development of new antimicrobial agents.
Keywords: Iminothiazolidinones; Multicomponent reaction; Antibacterial activity; Cytotoxicity; HEK-293; BIOLOGICAL-ACTIVITY; THIAZOLIDINONES; INHIBITORS; TARGET; Chemistry